Pozos de ambición - Anderson, Paul Thomas; Anderson, Paul Thomas; Anderson, Paul Thomas; Dano, Paul, 1984-; Day-Lewis, Daniel; Freasier, Dillon, 1996-; Hinds, Ciaran; Lupi, Daniel; O'Connor, Kevin J., 1964-; Sellar, Joanne; Sinclair, Upton, 1878-1968 (Paramount Vantage, 2007)
Carácter de un estudio de 1910 del pionero de petróleo y su despiadada adquisición de la riqueza y el poder.